Formation of young massive star clusters: a high-resolution multi-wavelength study of intensely star-formation galaxies - Randriamanakoto, Rojovola Zara-Nomena (Department of Astronomy, 2015)
Super star clusters (SSCs) represent the youngest and most massive form of known gravitationally bound star clusters in the Universe. They are born abundantly in environments that trigger strong and violent star formation (SF) such as in galaxy mergers and interacting systems. SSCs are thus used as fundamental tools to understand the context of massive SF and galaxy evolution in general. This thesis investigates properties of these young, massive and dense star clusters in a sample of 42 nearby starbursts and luminous infrared galaxies (LIRGs) ...